Spillover effect of children’s education on parental physical functioning over the life course - Dan Chen (Scientific Reports)
Abstract Parental well-being is linked to the life chances of adult children in later life. Despite accumulated knowledge on the role of children’s education on parental longevity in developed contexts, it remains unknown how children’s education may influence the trajectories of parental physical well-being over the aging process, particularly in developing contexts. Using a growth curve model and four-wave data from the China Health and Retirement Longitudinal Study, this study examines the association between children’s education and parental physical functioning trajectories as parents age. This study yields several findings. First, adult children’s schooling is negatively associated with the limited physical functioning of older parents. Second, consistent with the cumulative disadvantage perspective, this study confirms the diverging parental health trajectories across different children’s education groups as parents age. The linear rate of decline in parental physical functioning is slower among older adults with better-educated children. Third, the education returns of sons and daughters with regard to their parents’ physical functioning are similar to each other, implying the rationale for gender-blind attitudes in parenthood. Fourth, children’s education has a compensatory effect among parents lacking institutional old-age support. The association between children’s education and parental physical functioning is significant among rural older adults only.